The influence of selected oenological practices on the sensory impact of volatile phenols in red wines - Barbosa, Antonina (2013)
Aims: Volatile phenols (4-ethylphenol and 4-ethylguaiacol) affect wine quality by imparting, above certain concentrations, aroma defects. This work aimed to evaluate the effect of some common oenological practices on the concentration of volatile phenols and the sensory impact of these odour-active compounds in wines. Methods and results: The studied oenological practices were based on the addition of gum arabic, mannoproteins, yeast cell walls, lees, oak chips, dairy cream and potassium caseinate and on the application of a bubbled nitrogen stream. These treatments were applied to naturally contaminated wines containing volatile phenols at concentrations above detection threshold. The treated wines were characterised by chemical and sensory analysis. The most effective treatments in the reduction of the concentration of volatile phenols were the addition of fine lees, cream and potassium caseinate. Apart from being able to partially remove these compounds (approximately 35% removal), fine lees contributed to a greater “freshness” and complexity of the wines. Although the addition of cream did decrease the sensory impact of volatile phenols, it did not benefit the wines as these were strongly marked by dairy aromas. The use of oak chips, although it did not have a notable effect on the removal of volatile phenols, led to a significant reduction in the perception of these compounds.